1997
DOI: 10.1023/a:1026338827266
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the Coat Protein of a New Tobacco Mosaic Virus Coat Protein ts-Mutant

Abstract: Amino acid substitutions in a majority of tobacco mosaic virus (TMV) coat protein (CP) ts-mutants have previously been mapped to the same region of the CP molecule tertiary structure, located at a distance of about 70 A from TMV virion axis. In the present work some properties of a new TMV CP ts-mutant ts21-66 (two substitutions I21=>T and D66=>G, both in the 70-A region) were studied. Thermal inactivation characteristics, sedimentation properties, circular dichroism spectra, and modification by a lysine-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…As was mentioned in Section l, at pH 8.0 and low ionic strength TMV CP exists in the form of small (3 or 4S) Aprotein aggregates (see also Table 1). Previously we reported that ts21-66 CP in the form of the A-protein by several criteria displays a somewhat lower thermostability than wildtype (U l) CP [9] and behaves in this respect like CPs of the other mutants of this type [13,14]. This conclusion was confirmed by the results of DSC experiments.…”
Section: Dsc Melting Of Coat Protein Aggregates and Tmv Virions At MIsupporting
confidence: 71%
See 2 more Smart Citations
“…As was mentioned in Section l, at pH 8.0 and low ionic strength TMV CP exists in the form of small (3 or 4S) Aprotein aggregates (see also Table 1). Previously we reported that ts21-66 CP in the form of the A-protein by several criteria displays a somewhat lower thermostability than wildtype (U l) CP [9] and behaves in this respect like CPs of the other mutants of this type [13,14]. This conclusion was confirmed by the results of DSC experiments.…”
Section: Dsc Melting Of Coat Protein Aggregates and Tmv Virions At MIsupporting
confidence: 71%
“…A large size of the heat absorption peak at 38 or 41°C and an absence of additional peaks at higher temperatures testify against our previous suggestion [9], that only partial denaturation of U1 and ts21-66 CPs takes place at these low temperatures and prove that complete denaturation of TMV CP has occurred. Thus, at pH 8.0 TMV CP displays surprisingly low thermostability.…”
Section: Dsc Melting Of Coat Protein Aggregates and Tmv Virions At MIsupporting
confidence: 68%
See 1 more Smart Citation
“…Wild type (strain U1) TMV was obtained as described elsewhere [11] and its coat protein was isolated by the acetic acid method [12]. The CP preparations were stored at concen trations of 4 to 5 mg/ml in 5 mM Na/Na phosphate buffer (PB), pH 8.0, at 4 or -20°C.…”
Section: Purification Of Viruses and Cp Preparationmentioning
confidence: 99%
“…Underlined amino acid replacements cause temperature sensitivity of the subunit, non‐underlined ones do not ([8–10,12]; cf. [18]).…”
Section: Introductionmentioning
confidence: 99%